DESIGN OF HUMAN RESOURCES MANAGEMENT SYSTEM AT A CONSULTING SERVICE COMPANY FOR WATER RESOURCES INFRASTRUCTURE IN INDONESIA - Abdurrahman, Gani; Harianto, Eric; Sutanto, J.E. (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This study aims to obtain a balanced scorecard system concept design that is in accordance with the vision and mission of PT. Wecon which is engaged in consulting services for dam construction in the territory of Indonesia. This research method uses descriptive qualitative method with triangulation technique. This study uses informants consisting of 3 management people, 1 association from similar companies, 1 expert who understands in designing the balance scorecard of a consulting service company. This research was conducted from December 2021 to July 2022. The first stage will begin with a SWOT analysis. From the results of the analysis, it can be seen that the company is in a condition that requires quality human resources so that in the future the company must develop a strategy that must be done. In the next stage, measurements are carried out based on the perspective of the policy model to be implemented in a work program that includes four aspects of financial, customer, internal business, growth and learning. Based on the process hierarchy analysis method, it is found that the customer perspective will be the first priority, then followed by the financial, internal business, and learning and growth perspectives. customer needs, increase cooperation with local and international companies, provide training and certification for employees.